2002
DOI: 10.1021/ma020973e
|View full text |Cite
|
Sign up to set email alerts
|

Gelation Mechanism of Syndiotactic Polystyrene in Bromoform

Abstract: The gelation of sPS in bromoform was investigated with different techniques. Calorimetric results allowed to conclude that bromoform acts as a good solvent for sPS and that at low polymer concentration the formation of very strong, elastic gels is possible without interaction with the crystallization of the polymer. The conformational transition from coil into helix was followed by means of infrared measurements. The mobility change of the polymer chain during the transition was monitored by 1 H NMR. These res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 28 publications
2
34
0
Order By: Relevance
“…The gel is formed by a mechanism combining an intramolecular conformational transition of coil into helix with an intermolecular association forming a network. [19] But up to now no conclusion could be drawn about the morphology of these cross-links. The gels reach their maximal G 0 value when they are prepared at 30 8C.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The gel is formed by a mechanism combining an intramolecular conformational transition of coil into helix with an intermolecular association forming a network. [19] But up to now no conclusion could be drawn about the morphology of these cross-links. The gels reach their maximal G 0 value when they are prepared at 30 8C.…”
Section: Discussionmentioning
confidence: 99%
“…This is not what is observed when such gels are formed in good solvents. [19,21] A possible explanation could be the vicinity of the liquidliquid demixing domain that will inevitably lead to an important increase in the concentration fluctuations. These fluctuations can cause a decrease in the quality of the obtained network and hence of the modulus of the gel.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Recent studies in the temperature-concentration phase diagrams of sPS gels have suggested that solvent molecules are intercalated between sPS chains in the TTGG conformation, and the number of solvent molecules involved is dependent on the gelation solvent. [7][8][9][10][11] The ordered TT conformation was observed on gelation of sPS in big size solvent like octadecyl benzoate. 12 Time-resolved small-angle neutron scattering (SANS) experiments also showed that the gelnetwork structure formation occurred in parallel to the conformational ordering of sPS chains.…”
mentioning
confidence: 99%